ZnFe2O4-TiO2 Nanoparticles within Mesoporous MCM-41 - Aidong Tang; Yuehua Deng; Jiao Jin; Huaming Yang (The Scientific World Journal)
A novel nanocomposite ZnFe2O4-TiO2/MCM-41 (ZTM) was synthesized by a sol-gel method and characterized through X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), N2 adsorption-desorption, Raman spectroscopy, and ultraviolet visible (UV-vis) spectrophotometry. The results confirmed the incorporation of ZnFe2O4-TiO2 nanoparticles inside the pores of the mesoporous MCM-41 host without destroying its integrity. ZnFe2O4 nanoparticles can inhibit the transformation of anatase into rutile phase of TiO2. Incorporation of ZnFe2O4-TiO2 within MCM-41 avoided the agglomeration of nanoparticles and reduced the band gap energy of TiO2 to enhance its visible light photocatalytic activity. UV-vis absorption edges of ZTM nanocomposites redshifted with the increase of Zn/Ti molar ratio. The nanocomposite approach could be a potential choice for enhancing the photoactivity of TiO2, indicating an interesting application in the photodegradation and photoelectric fields.